A Broadcast Engineering Tutorial for Non-Engineers. - Pizzi, Skip (Taylor and Francis, 2014)
"A Broadcast Engineering Tutorial for Non-Engineers is the leading publication on the basics of broadcast technology. Whether you are new to the industry or do not have an engineering background, this book will give you a comprehensive primer of television, radio, and digital media relating to broadcast--it is your guide to understanding the technical world of radio and television broadcast engineering. It covers all the important topics such as DTV, IBOC ('HD Radio'), cable and satellite radio and television, digital audio and video standards, broadcast studio and remote facilities, radio frequency coding and modulation, video servers, editing, electronic newsrooms, surround sound, streaming media, broadcast regulation and more. Important updates! This long-awaited fourth edition has been completely revised and includes substantial new material on emerging digital technologies that are revolutionizing the industry, such as: HDTV--and 'UltraHD'; IP-based content production, distribution, and delivery (including 'over-the-top' TV); Connected/Smart TV, Mobile TV, Second Screens, and Social TV; 'Hybrid' broadcasting (over-the-air and online convergence); Content protection (Conditional Access and Digital Rights Management); Podcasting, Mobile Apps, and Connected Cars; Next-generation radio and television services around the world"--